Operational control of an integrated drum boiler of a coal fired thermal power plant. (15th September 2018) - Chandrasekharan, Sreepradha; Panda, Rames C.; Swaminathan, Bhuvaneswari Natrajan; Panda, Atanu
Abstract: Boiler in thermal-power-plant plays important role in generation of power. Conventional subcritical-boilers use single-loop controls which are less efficient. An effective control of temperature and pressure of boiler is necessary to enable safe power generation. This article discusses application of three different multivariable-control strategies, namely, PID (Proportional-Integral- Derivative), MPC (Model Predictive Controller) and Inverse-decoupling-control to the individual units of boiler (economizer, drum, super-heater) as well as to the integrated boiler unit of the coal-fired thermal-power-plant separately. The mathematical-model derived based on mass-balance and energy-balance equations of economizer, drum and superheater units are used for the synthesis of controller. The non-square nature of mathematical-model carries complexity in the design of controllers. The performances, based on minimization of objective-function containing closed-loop error along with the control-effort of individual and integrated units, of the boiler using IMC (Internal-Model-Control) based PID, Inverse-decouple and MPC in the presence of disturbances are analyzed and compared. The results show that multi-loop control of integrated units ensures asymptotic-stability compared to unstable single-loop control and the controller needs to take less effort in the case of the integrated unit compared to the individual units. The results suggest for implementation of integrated multi-loop control instead of controlling individual boiler units. Graphical abstract: Image Highlights: A mathematical model for the integrated components of boiler is formulated. The model based on plant data is used to formulate objective functions for MPC. Multi-loop PID, MPC, Inverse decoupling synthesized & implemented for first time. Control effort is less for inverse decoupling for integrated compared to individual.